Adherence therapy versus routine psychiatric care for people with schizophrenia spectrum disorders: a randomised controlled trial. Issue 1 (December 2016) - Chien, Wai; Mui, Jolene; Gray, Richard; Cheung, Eric
Abstract Background Current practice guidelines for schizophrenia care recommend that antipsychotic medication is essential for patients' long-term maintenance treatment but their non-adherence to this medication is still a main obstacle to relapse prevention. This study evaluated the effects of a motivational-interviewing-based adherence therapy for people with schizophrenia spectrum disorders. Methods This randomised controlled trial was conducted with 134 outpatients with schizophrenia spectrum disorders; 67 of them received a six-session adherence therapy (in addition to usual care) and 67 received usual psychiatric care alone. Participants' outcome measures included symptom severity, medication adherence, hospitalisation rates, insight into illness/treatment, and functioning. Results The adherence therapy group reported significantly greater improvements in symptom severity (p < 0.003), insight into illness/treatment (p < 0.001), functioning (p < 0.005), duration of re-hospitalisations (p < 0.005), and medication adherence (p < 0.005) over 18 months follow-up, when compared with usual care alone. Conclusions Motivational-interviewing-based adherence therapy can be an effective approach to treatment for people with early stage of schizophrenia who poorly adhere to medication regimen. Trial registration ClinicalTrials.govNCT01780116, registration date January 29, 2013.